Effect of diet restriction on work performance and weight loss of local Zebu and Friesian X Boran crossbred oxen - Astatke, A.; Reed, J.D.; Butterworth, M.H. (1986)
Reports results of an experiment conducted to determine the effect of diet restriction on work performance and body weight in crossbred and local oxen worked as singles in farmers' fields around Debre Zeit, Ethiopia, during the normal cultivation season.